2012
DOI: 10.1111/j.1365-2958.2012.08093.x
|View full text |Cite
|
Sign up to set email alerts
|

Francisella tularensis tmRNA system mutants are vulnerable to stress, avirulent in mice, and provide effective immune protection

Abstract: Through targeted inactivation of the ssrA and smpB genes, we establish that the trans-translation process is necessary for normal growth, adaptation to cellular stress, and virulence by the bacterial pathogen Francisella tularensis. The mutant bacteria grow slower, have reduced resistance to heat and cold shocks, and are more sensitive to oxidative stress and sub-lethal concentrations of antibiotics. Modifications of the tmRNA tag and use of higher resolution mass spectrometry approaches enabled the identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
31
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 73 publications
(111 reference statements)
7
31
2
Order By: Relevance
“…In fact, trans-translation is essential in some species, including Shigella flexneri, Helicobacter pylori, Neisseria gonorrheae, and Mycoplasma species (14)(15)(16)(17). In addition, mutants lacking trans-translation activity are avirulent in Salmonella enterica, Yersinia pestis, Streptococcus pneumoniae, and Francisella tularensis (18)(19)(20)(21), so inhibitors of the pathway could be effective against a wide array of pathogens. We identified compounds that inhibit trans-translation using a high-throughput screen (HTS) and demonstrated that these compounds have antibiotic activity.…”
mentioning
confidence: 99%
“…In fact, trans-translation is essential in some species, including Shigella flexneri, Helicobacter pylori, Neisseria gonorrheae, and Mycoplasma species (14)(15)(16)(17). In addition, mutants lacking trans-translation activity are avirulent in Salmonella enterica, Yersinia pestis, Streptococcus pneumoniae, and Francisella tularensis (18)(19)(20)(21), so inhibitors of the pathway could be effective against a wide array of pathogens. We identified compounds that inhibit trans-translation using a high-throughput screen (HTS) and demonstrated that these compounds have antibiotic activity.…”
mentioning
confidence: 99%
“…We can use the method for monitoring of stress state with very good results. From a literature search, F. tularensis is quite resistant to oxidative stress and it can recovery from stress conditions more easily than the host organism 36 . IFN-was assessed in plasma samples (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Svetlanov et al have shown that F. tularensis mutants lacking tmRNA or SmpB are viable but grow slowly, are more sensitive to stress, and have attenuated virulence (16). If these F. tularensis mutants with no trans-translation activity can survive, why is the growth of wild-type bacteria completely stopped by KKL-10 and KKL-40, which inhibit ribosome rescue?…”
Section: Discussionmentioning
confidence: 99%
“…This reaction also targets the nascent polypeptide and mRNA for degradation (10)(11)(12)(13). F. tularensis mutants lacking SmpB or tmRNA are attenuated for virulence in mouse models (16). Some bacteria, such as Escherichia coli, can survive without trans-translation because they contain ArfA, a protein that allows release factor 2 (RF-2) to terminate translation on ribosomes stalled at the 3= end of an mRNA (17)(18)(19).…”
mentioning
confidence: 99%
See 1 more Smart Citation